Delamination and Photochemical Modification of a Novel Two‐Dimensional Zr‐Based Metal–Organic Frameworks. Issue 49 (17th August 2018) - Mohmeyer, Alexander; Schaate, Andreas; Brechtken, Benedikt; Rode, Johannes C.; Warwas, Dawid P.; Zahn, Gesa; Haug, Rolf J.; Behrens, Peter
Abstract: In this contribution we present a novel two‐dimensional Zr‐based metal–organic framework (MOF) which offers the possibility for delamination and post‐synthetic photochemical modification at the linker molecule derived from benzophenone‐4, 4′‐dicarboxylic acid (H2 bzpdc ). The new Zr‐ bzpdc ‐MOF crystallizes in the orthorhombic system as crystals with rhombic shape. The structure was determined from single‐crystal diffraction data. The MOF is stable up to 300 °C in air and exhibits a moderate BET surface area of 650 m 2 g −1 . The material can be obtained as thin sheets of a few nanometer thickness. Single crystals were modified post‐synthetically, exploiting the intrinsic reactivity of the benzophenone group with C−H bond containing molecules. In this way, the surface properties of the MOF crystals (e.g., dispersibility in different solvents) can be changed drastically. Delamination and adaptation of the surface chemistry open up novel ways for shaping MOFs, for example, for the incorporation into polymer composites, and pave the way for various applications. Abstract : The novel two‐dimensional Zr‐based metal–organic framework (MOF) with the photochemically active linker benzophenone‐dicarboxylic acid and its delamination and surface chemistry at the linker molecules open up novel ways for shaping MOFs and pave the way for various applications.